2021
DOI: 10.1016/j.isci.2021.102934
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric degrees of freedom determining thermoelectric efficiency

Abstract: Summary For over half a century, the development of thermoelectric materials has based on the dimensionless figure of merit , assuming that the efficiency is mainly determined by this single parameter. Here, we show that the thermoelectric conversion efficiency is determined by three independent parameters, , τ , and β , which we call the three thermoelectric degrees of freedom (DoFs). is t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 282 publications
(162 reference statements)
0
15
0
Order By: Relevance
“…However, Equation (6) is based on a constant property model (CPM) using averaged values of temperature-dependent material properties [ 57 ]. Secondly, CPM neglects further relevant impacts on the operation and performance of TEMs, such as Thomson heat, asymmetric distribution of Joule heat, electric and thermal contact resistances, and the presence of parasitic heat bypasses by means of radiation or convection [ 58 ], which yields approximated values for η only. Armstrong et al [ 59 ] studied the performance determination for 18 TE materials and showed an overestimated prediction of η (by an average factor 1.16) by CPM compared to a cumulative model, which was proposed earlier by Kim et al [ 60 ] to account for the temperature dependence of material properties by means of the so-called “engineering figure of merit”.…”
Section: Methodsmentioning
confidence: 99%
“…However, Equation (6) is based on a constant property model (CPM) using averaged values of temperature-dependent material properties [ 57 ]. Secondly, CPM neglects further relevant impacts on the operation and performance of TEMs, such as Thomson heat, asymmetric distribution of Joule heat, electric and thermal contact resistances, and the presence of parasitic heat bypasses by means of radiation or convection [ 58 ], which yields approximated values for η only. Armstrong et al [ 59 ] studied the performance determination for 18 TE materials and showed an overestimated prediction of η (by an average factor 1.16) by CPM compared to a cumulative model, which was proposed earlier by Kim et al [ 60 ] to account for the temperature dependence of material properties by means of the so-called “engineering figure of merit”.…”
Section: Methodsmentioning
confidence: 99%
“…However, little is known about the current status of device efficiency. The efficiency estimation using 𝑍𝑇 is not very accurate for wide-temperature-range applications 12 because TEPs are temperature dependent. Additionally, the estimation ignores several factors introduced in device fabrication processes.…”
Section: Main Textmentioning
confidence: 99%
“…when 𝑇 ? =300 K. The thermoelectric efficiency is computed by solving one-dimensional thermoelectric integral equations for the temperature distribution 𝑇(𝑥) and heat currents at the hot and cold sides 12,14 . Using the searched high-performance P-and N-leg samples, of which the efficiency is larger than or equal to 85% of the best efficiency, single-stage P-N leg-pair devices with various leg geometries and interfacial resistances are constructed.…”
Section: Main Textmentioning
confidence: 99%
“…The Seebeck effect and conversion efficiency are important in thermoelectric energy harvesting technology. The thermoelectric dimensionless figure of merit (ZT) is defined as ZT = α 2 σT/κ, where α is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature [9,10]. The thermoelectric conversion efficiency (η) is defined as η = P out /Q h , where P out is the electric output power and Q h is the heat input [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The thermoelectric dimensionless figure of merit (ZT) is defined as ZT = α 2 σT/κ, where α is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature [9,10]. The thermoelectric conversion efficiency (η) is defined as η = P out /Q h , where P out is the electric output power and Q h is the heat input [9,10]. Many researchers have investigated thermoelectric materials with high ZT and η for applications in thermoelectric energy harvesting [6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%